2017
DOI: 10.1177/1741659017736097
|View full text |Cite
|
Sign up to set email alerts
|

Private prisons and the management of scandal

Abstract: In 2009, the Corrections (Contract Management of Prisons) Amendment Act re-implemented prison privatisation in New Zealand (NZ). Subsequently, ‘Mt Eden’, a public prison, was contracted to Serco and a second prison, ‘Wiri’, was built under contract to the same company. Despite glowing performance reports, Serco’s reputation was significantly damaged when cell-phone video capturing Mt Eden prisoners engaged in fights, in full view of prison officers and CCTV, was uploaded to YouTube in July 2015. An unprecedent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…At the end of GEO's initial contract, therefore, the prison became part of the public‐sector system. Then, in 2008, the incoming Conservative Government introduced the Corrections (Contract Management of Prisons) Amendment Act 2009 , allowing competitive tendering and private‐sector operation of prisons (Boyle & Stanley, ; Chan, ; Kenter & Prior, ). Mount Eden prison was put out for tender again.…”
Section: Other Jurisdictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of GEO's initial contract, therefore, the prison became part of the public‐sector system. Then, in 2008, the incoming Conservative Government introduced the Corrections (Contract Management of Prisons) Amendment Act 2009 , allowing competitive tendering and private‐sector operation of prisons (Boyle & Stanley, ; Chan, ; Kenter & Prior, ). Mount Eden prison was put out for tender again.…”
Section: Other Jurisdictionsmentioning
confidence: 99%
“…Mount Eden prison was put out for tender again. This time Serco was successful, and the new contract was packaged into a larger contract for the Mount Eden Correctional Facility in 2012 (Boyle & Stanley, ; Mason, ).…”
Section: Other Jurisdictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside these accounts have been efforts by scholars to examine how the media portray crime and justice issues (Blakely & Bumphus, 2005b; Boyle & Stanley, 2019; Burkhardt, 2014; Dixon & Williams, 2014; Pollak & Kubrin, 2007). A central finding of this work has been that the media frequently oversimplify dimensions that may bear on discussions about policies aimed at crime, criminal justice, and corrections (see generally, Carlyle et al, 2008; Chermak, 1994; Dixon & Williams, 2014; Marsh, 1991; Pollak & Kubrin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Burkhardt’s (2014) content analysis found that states that did not discuss privatization as a moral issue were more likely to use privatization, as compared with states that focused on the morality of the practice. A third exception is Boyle and Stanley’s (2019) analysis of New Zealand news articles published after a series of revelations about the mistreatment of individuals incarcerated at a private prison. They found that the topic that dominated news stories was the “economic and bureaucratic management of prisons”; fewer studies focused on politics, security, humanitarianism, or social or symbolic exclusion of incarcerated individuals (Boyle and Stanley, 2019, p. 74).…”
Section: Introductionmentioning
confidence: 99%